Comparative Treatment Outcome in T3N0 Glottic Cancer With and Without Vocal Fold Fixation Receiving Radiation Therapy and Concurrent Low-Dose Intra-Arterial Cisplatin Infusion. (August 2022) - Ono, Takeharu; Tanaka, Norimitsu; Chitose, Shun-ichi; Tanoue, Syuichi; Kurita, Takashi; Sueyoshi, Shintarou; Fukahori, Mioko; Miyata, Yusaku; Muraki, Koichiro; Tsuji, Chiyoko; Ogo, Etsuyo; Hattori, Chikayuki; et al.
Objectives: Selective radiotherapy and concomitant intra-arterial cisplatin infusion (m-RADPLAT) with a lower cisplatin dosage have been performed for organ and function preservation in patients with locally advanced squamous cell carcinoma of the larynx (SCC-L), and results showing a lower rate of adverse events have been reported. This study evaluated the treatment outcomes of patients with T3N0 glottic SCC-L with or without vocal fold fixation (VFF) who were treated with m-RADPLAT. Methods: We retrospectively reviewed the data of 33 patients with T3N0 SCC-L who received m-RADPLAT. Results: The vocal fold in patients with VFF 3 months after completing m-RADPLAT resumed normal movement in 15 patients (83%) and persisted fixation in 3 (17%). The 3-year local control, laryngeal cancer-specific survival, and overall survival rates of patients with or without VFF were 88.9% and 86.7%, 94.1% and 93.3%, and 88.9% and 86.7%, respectively. Additionally, the 3-year freedom from laryngectomy, laryngectomy-free survival, and laryngo-esophageal dysfunction-free survival rates of patients with or without VFF were 94.4% and 86.7%, 88.9% and 73.3%, and 83.3% and 73.3%, respectively. Grade 3 or higher toxicities were observed in all patients: leukopenia in 4 patients (12%), neutropenia in 5 (15%), anemia in 2 (6%), thrombocytopenia in 3 (9%), and mucositis in 2 (6%). Conclusions: This study demonstrated that m-RADPLAT yielded VFF improvement and a favorable survival while maintaining laryngeal function not only in patients with T3N0 glottic SCC-L without VFF but also in patients with VFF.